2009
DOI: 10.1039/b815986f
|View full text |Cite
|
Sign up to set email alerts
|

The development of an environmentally benign sulfideoxidation procedure and its assessment by green chemistry metrics

Abstract: Different Iron (III) species were used as catalysts in sulfoxidation reactions giving excellent yields and high chemoselectivity. Among the iron (III) species, the best one was a solid b-cyclodextrin-FeBr 3 complex. Sulfoxidation takes place with high chemoselectivity in the presence of other groups such as isothiocyanate. Good results were obtained when these reactions were analyzed using green chemistry metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Some of these systems perform as catalysts for asymmetric sulfide oxidation, and a few can utilize dioxygen as the oxidant [34-60]. There are only a few reports of iron-based sulfoxidation catalysts, but all of these systems utilize Fe III centers in lieu of Fe II [41, 49, 51, 52]. Molecular O 2 is used in some of these cases as a co-oxidant with an Fe III source and an additional oxidant generated in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these systems perform as catalysts for asymmetric sulfide oxidation, and a few can utilize dioxygen as the oxidant [34-60]. There are only a few reports of iron-based sulfoxidation catalysts, but all of these systems utilize Fe III centers in lieu of Fe II [41, 49, 51, 52]. Molecular O 2 is used in some of these cases as a co-oxidant with an Fe III source and an additional oxidant generated in situ.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the reactions proceeded smoothly in aqueous medium with MgSO 4 (10 mol %) to produce the N,N 0 -unsubstituted bis-compounds in excellent yields (Scheme 2, Table 5). The reaction generated two new chiral centers at C 4 and C 4 0 -positions, the relative stereochemistry of which could be either RR or RS. X-ray crystallography of these compounds was not possible due to their amorphous nature.…”
Section: àmentioning
confidence: 99%
“…The green metrics were calculated using the procedures reported in the literature. 4 Their definitions are given as follows: Mass Intensity (MI) ¼ Total mass used in a process or process step (g)/mass of product (g) Reaction mass efficiency (RME) ¼ (R mass of products/R mass of reactants) Â 100 January 2010 139…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 1. In these studies, we observed that 4-(methylthio)aniline give as by-product 4-(methylthio)bromobenzene, suggesting the formation of a diazonium salt in the reaction media by diazotization of the aromatic amino group [34]. The behaviour of 4-(methylthio)aniline prompted us to explore potential applications of our catalytic system in the diazonium salt synthesis.…”
Section: Introductionmentioning
confidence: 96%